(untitled) (Nordic Journal of African Studies, 2005)
The main issue investigated in this study was what became of the interpersonal profile of the sampled population in view of their prevalent use of GSM phone, a communication enhancing technological device that came with the millennium encroachment of the global village. The dimensions of investigation covered interactional levels as existed between subjects and the significant others in their social space, value implication of GSM phone use on socio-cultural orientations, general survey of interactional patterns, and focus on gender as a possible predictor of the interaction between interpersonal competence and GSM phone use. Findings did not support any significant debilitating effect of the GSM phone use on interpersonal competence and appropriate socio-cultural norm compliance attitude among subjects, while the interpersonal disposition of respondents showed a positive bias for warmth and affiliation, significant traces of gender variations however existed when measured on certain criterion measures used in the study. On the aggregate, GSM phone use appeared to possess an interpersonal enhancing property which was able to reduce the effect of distance on communication values among social actors.